2019
DOI: 10.1097/meg.0000000000001513
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a capsule endoscope delivery device in children

Abstract: Objectives This multicenter, cross-sectional study aimed to elucidate the efficacy and safety of the AdvanCE capsule endoscope delivery device for children in Japan. Methods The present study analyzed 183 cases of small bowel capsule endoscope (SBCE) insertion performed using the AdvanCE in 154 patients aged less than 18 years at participating institutions between 2013 and 2017. Statistical analyses were conducted to identify factors contributing to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…[2][3][4][5] A multicenter, cross-sectional study including 183 patients aged <18 years demonstrated the successful delivery of SBCEs into the duodenum in 90% of patients without severe complications, with exceptions including an inability to deliver the capsule through the pharynx (n = 2) or the pylorus (n = 1). 6 Simon et al 7 reported a severe complication: small bowel perforation distal to the gastrojejunal anastomosis caused by AdvanCEbased delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] A multicenter, cross-sectional study including 183 patients aged <18 years demonstrated the successful delivery of SBCEs into the duodenum in 90% of patients without severe complications, with exceptions including an inability to deliver the capsule through the pharynx (n = 2) or the pylorus (n = 1). 6 Simon et al 7 reported a severe complication: small bowel perforation distal to the gastrojejunal anastomosis caused by AdvanCEbased delivery.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, endoscopic capsule placement is available using the AdvanCE delivery device (US Endoscopy Inc., Mentor, OH, USA), polypectomy snares, Roth nets, etc 2–5 . A multicenter, cross‐sectional study including 183 patients aged <18 years demonstrated the successful delivery of SBCEs into the duodenum in 90% of patients without severe complications, with exceptions including an inability to deliver the capsule through the pharynx ( n = 2) or the pylorus ( n = 1) 6 . Simon et al 7 .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the European Society of Gastrointestinal Endoscopy guidelines clearly state that the prior use of patency capsule is not required for obscure gastrointestinal bleeding ( 21 ). In addition, in younger children who cannot swallow or in patients with dysphagia, EGD guidance is required for the insertion of the capsule endoscope and patency capsule ( 22 ). In such cases, EGD must be performed twice, and its invasiveness should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, it was approved by the FDA. Over the years, its safety and effectiveness have been investigated extensively [15], [16], [17]. Wireless capsule endoscopy eliminates the need of using optical fibers or a CMOS camera via a tethered endoscope, which is bulky and often requires general anesthesia to examine the gastrointestinal (GI) tract.…”
Section: B Capsule Endoscopymentioning
confidence: 99%